NEUROETHICS IN THE ERA OF ARTIFICIAL INTELLIGENCE AND BRAIN TECHNOLOGIES: ETHICAL, LEGAL, AND SOCIETAL IMPLICATIONS OF EMERGING NEUROTECHNOLOGIES (Global Conference on Medical and Health Sciences, 2026)
The rapid advancement of artificial intelligence (AI) and brain technologies has given rise to complex ethical, legal, and societal challenges, forming the foundation of an emerging interdisciplinary field known as neuroethics. Innovations such as brain–computer interfaces, neuroimaging, and AI-driven neural data analysis are transforming neuroscience and clinical practice, enabling unprecedented access to brain function and cognitive processes. However, these developments also raise critical concerns regarding autonomy, privacy, identity, and responsibility.
Keywords: Neuroethics; Artificial intelligence; Brain–computer interface; Cognitive privacy; Neurotechnology; Ethical governance; AI ethics; Mental autonomy